Reconstructing Legal Accountability through Body-Worn Cameras: A Normative Study of Criminal Justice Reform in Indonesia - Naidah, Siti; Fernando, Zico Junius (UIN Sunan Kalijaga Yogyakarta, 2025)
Efforts to modernize Indonesia's criminal justice system demand legal mechanisms that ensure accountability, fairness, and human rights protection at every procedural stage. While global studies on Body-Worn Cameras (BWCs) have focused on operational and policing impacts, few have examined their normative legitimacy and evidentiary validity within Indonesia's legal context. Anchored in the principles of the rule of law, due process, and evidentiary integrity, this study analyzes the legal status of BWCs, explores comparative practices in other jurisdictions, and formulates an ideal regulatory model for Indonesia. This research employs a normative legal method using conceptual and comparative approaches, analyzing statutory materials, public policies, and international practices from the United States, the United Kingdom, Germany, and Australia. The findings reveal that Indonesia lacks a comprehensive legal framework governing operational standards, data management, and the evidentiary use of BWC recordings, resulting in uncertainty and fragmented practices. Comparative experiences show that BWCs become effective when legal systems ensure chain-of-custody integrity, privacy protection, and independent oversight. This study formulates a conceptual legal model integrating accountability, evidentiary reliability, and data protection through explicit activation rules, retention schedules, and dual accountability mechanisms involving internal and external oversight. Accordingly, BWCs are positioned not merely as technological devices but as instruments of legal reform that align Indonesia's criminal justice system with global standards of transparency, proportionality, and rights-based governance.